2016
DOI: 10.2139/ssrn.2939502
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pre-Opening Mechanisms in Fragmented Markets

Abstract: and CEPR 4 1 We are very grateful to Paul Besson (from Kepler-Chevreux), Dion Bongaerts, Catherine d'Hondt, Thierry Foucault, Carole Gresse, Alexander Guembel, Marius Zoican and seminar participants at the 3rd Forum "Market Microstructure: Confronting Many Viewpoints" (Paris) for providing useful comments. We especially thank Eurofidai-Bedofih for providing us the data. Laurence Lescourret is research fellow at CREST. Financial support from the ANR (ANR-16-CE26-0008) is gratefully acknowledged. Part of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Gu et al (2010) report that the average density of the auction limit order book on both sides of the final auction price is well fitted by an exponential distribution and compute the persistence fluctuation properties of the order size in the Shenzhen Stock Exchange. More recently, and more in line with our paper, Boussetta et al (2016) study the French Stock exchange and find that different kind of market participants enter the pre-auction periods at markedly different times, the slow brokers acting first, while high-frequency traders tend to be active nearer the end of auctions. In the same vein, Bellia et al (2016) show how and when low-latency traders (identified as high frequency traders) add or remove liquidity in the pre-opening auction of the Tokyo Stock Exchange.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Gu et al (2010) report that the average density of the auction limit order book on both sides of the final auction price is well fitted by an exponential distribution and compute the persistence fluctuation properties of the order size in the Shenzhen Stock Exchange. More recently, and more in line with our paper, Boussetta et al (2016) study the French Stock exchange and find that different kind of market participants enter the pre-auction periods at markedly different times, the slow brokers acting first, while high-frequency traders tend to be active nearer the end of auctions. In the same vein, Bellia et al (2016) show how and when low-latency traders (identified as high frequency traders) add or remove liquidity in the pre-opening auction of the Tokyo Stock Exchange.…”
Section: Introductionsupporting
confidence: 80%
“…Second, sending an order to an auction reveals some information about one's intentions, thus there is a clear strategic aspect to the time of order submission or cancellation. In other words, early orders may trigger a different response than later ones simply because the traders who submit the former have different strategies or expectations than the latter ones and may or may not cancel some of their orders before the auction ending time, in line with Boussetta et al (2016).…”
Section: Response Functionsmentioning
confidence: 99%
“…Only a handful of papers are devoted to the dynamics of auction phases, i.e., periods during which market participants may send limit or market orders specifically for the auction. Boussetta et al [2016] investigate when fast and slow traders send their orders during the opening auction phase of the Paris Stock Exchange and find markedly different behaviors: the slow brokers are active first, while highfrequency traders are mostly active near the end of auctions. In the same vein, Bellia et al [2016] show how and when low-latency traders (identified as high frequency traders) add or remove liquidity in the pre-opening auction of the Tokyo Stock Ex-…”
mentioning
confidence: 99%
“…At the intra-day level, the stock prices respond largely to information change and microstructure factors, such as transaction costs, blockages, and the complexities of price discovery. Biais et al (1999) show that as market opening gets closer, the informational content and efficiency of prices increase, and the learning hypothesis is not rejected (see Boussetta et al, 2017 for a study on the role of pre-opening mechanisms in fragmented markets). We focus on the market quality metrics related to the short-term volatility in a fragmented market to assess the evolution of the intraday market efficiency at market opening in the post-MiFID environment.…”
Section: Literature Reviewmentioning
confidence: 99%